Reprogramming Nonribosomal Peptide Synthesis by Surgical Mutation - Niquille, David L.; Hansen, Douglas A.; Hilvert, Donald (Synlett, 2019)
Nonribosomal peptide synthetases produce highly modified bioactive peptides, many of which are used therapeutically. As such, they have been the target of intense protein engineering to enable biosynthetic access to peptide variants with improved drug properties or altered bioactivities. In this account, we describe our ongoing efforts to reprogram nonribosomal peptide synthesis by surgical mutation. In contrast to ribosomal biosynthesis, nonribosomal peptide synthesis has proven difficult to engineer, arguably due to a lack of suitable tools. To address this limitation, we have established a high-throughput assay that provides unprecedented control over the gatekeeper adenylation domains responsible for building block selection and incorporation. Expansion of this strategy to other building blocks and domains promises to make it a powerful evolutionary platform for tailoring assembly lines for custom synthesis of peptide therapeutics.1. Nonribosomal Peptides2. Reprogramming A Domains for Clickable Amino Acids3 A High-Throughput A Domain Assay4 Reprogramming A Domains for β-Amino Acids5 Downstream Processing6 Conclusions and Outlook
Keywords: nonribosomal peptides; biosynthesis; high-throughput screening; bioorthogonal chemistry; β-amino acids; synthetic biology